Exploring the implementation of low carbon education and environmental care character in primary schools - Yulsy Marselina Nitte; Kristina E. Noya Nahak (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2026)
This research is motivated by the limitations of the study of low carbon education (LCE) in elementary schools that have not in-depth studied the process of interpretation and its integration with the value of caring for the environment. This research aims to explore how LCE is interpreted, implemented, and internalized in elementary school learning. The research uses a qualitative approach with a descriptive-interpretive design. The subjects consisted of 100 students and 20 teachers from 10 elementary schools in Kupang City who were selected purposively. Data were collected through interviews, observations, documentation, and questionnaires as support. The analysis is carried out through data reduction, presentation, and conclusion drawing by triangulating sources and methods to maintain credibility. The results show that LCE is interpreted through the integration of contextual learning, behavioral habituation, and sustainability-oriented school culture. The practice of low-carbon behavior in students is influenced by learning experiences, teacher examples, and the school environment. Teachers interpret LCE as an interdisciplinary approach that integrates knowledge, values, and actions. This research contributes to the strengthening of character-based LCE conceptual frameworks in elementary schools and provides practical implications for the development of contextual learning that supports pro-environmental behaviors.